Internet Usage and Communication Behaviour Among Academic and Non-Academic Female Staff in Three Malaysian Universities - Ahmed, Syeda Tasmina (2001)
In the Internet world the fastest growing audience is women. Apart from the limitless wonderment about the technical capabilities, the Internet has stimulated grave concern about its social impact as it is alleged to affect social relationships since Internet users are said to spend less time communicating with family and friends. Though Malaysia is a nation entering the information age with women constituting half of its population, no study has yet been done to investigate this issue. Therefore, this study was conducted specifically to determine (1) working women's communication behaviour at home and the workplace, (2) the differences in communication behaviour between female Internet users and nonusers, (3) pattern of Internet usage among female Internet users, (4) changes in communication time at home and the workplace and the relationship between time spent for Internet and changes in time for communication, (5) the most effective demographic characteristics to discriminate between Internet users and non-users; (6) reasons for not using Internet for the women who have Internet access. The study was conducted on the academic and non-academic staff in three universities in the Klang Valley. Responses from 327 subjects were finally used for the study. Findings of the present study do not substantiate the fact that Internet users spend less time communicating at home or the workplace. Rather, compared to Internet non-users, they are found to spend more time communicating with children. In communication behaviour, differences between users and non-users were detected in communicating some topics and in usage of some modes of communication. For communication in personal or working life, there is no indication that time spent for Internet has any negative relation with the change in time spent for communication. However, time spent for Internet is found to be negatively related with the change in time for using some modes and media. Discriminant analysis shows that the three most effective demographic variables to differentiate between Internet users and non-users are education level, having studying children, and age. The variable, having studying children has been identified as a new discriminant demographic variable as compared to the characteristics of adopters in the existing technology adoption model. Pornography in Internet is the most frequently cited reason for not using the Internet.